Motivasi Belajar Siswa Pada Materi Pecahan Kelas 5 SD 1 Piji Kabupaten Kudus - DAMAYANTI, SUWATI EKA; FAJRIE, NUR; KURNIATI, DIAH (Tunas Nusantara, 2024)
Mathematics is one of the compulsory subjects in elementary school which aims to train students' ability to think critically. Often students experience learning difficulties, both those caused by factors from the teacher and from the students themselves. Therefore, as a learning director, the teacher should be clever and creative in designing teaching and learning activities so that the learning objectives are expected to be achieved. One of the ways that teachers can package learning is to foster motivation in students so that students have the urge to carry out activities to achieve these learning goals. Mathematics KIT props can be an alternative learning media in learning math fraction material, it is hoped that the use of these props can increase extrinsic motivation in students. The purpose of this study was to determine student motivation The method used in this study was to determine student learning motivation on fraction material through Mathematics KIT props in Class 5 SD 1 Piji, Kudus Regency. The method used is qualitative research with a narrative approach. Data collection techniques through observation and interviews. The results of this study indicate that through the use of KIT Math props student learning motivation looks good. The conclusion of this study is that good learning motivation in grade 5 students in the mathematics subject of fraction material through KIT Mathematics props.